Water Electrolysis for the Production of Hydrogen to Be Employed in the Ironmaking and Steelmaking Industry - Pasquale Daniele Cavaliere (MDPI AG, 2021)
The way to decarbonization will be characterized by the huge production of hydrogen through sustainable routes. Thus, the basic production way is water electrolysis sustained by renewable energy sources allowing for obtaining “green hydrogen”. The present paper reviews the main available technologies for the water electrolysis finalized to the hydrogen production. We describe the fundamental of water electrolysis and the problems related to purification and/or desalinization of water before electrolysis. As a matter of fact, we describe the energy efficiency issues with particular attention to the potential application in the steel industry. The fundamental aspects related to the choice of high-temperature or low-temperature technologies are analyzed.